The evaluation of a stepped care approach for early intervention of borderline personality disorder - Cavelti, Marialuisa; Blaha, Yasmine; Lerch, Stefan; Hertel, Christian; Berger, Thomas; Reichl, Corinna; Koenig, Julian; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2024)
Background: The current study evaluated the stepped care approach applied in AtR!Sk; a specialized outpatient clinic for adolescents with BPD features that offers a brief psychotherapeutic intervention (Cutting Down Program; CDP) to all patients, followed by a more intensive Dialectical Behavioral Therapy for Adolescents (DBT-A) for those whose symptoms persist. Methods: The sample consisted of 127 patients recruited from two AtR!Sk clinics. The number of BPD criteria, psychosocial functioning, severity of overall psychopathology, number of days with non-suicidal self-injury (NSSI; past month), and the number of suicide attempts (last 3 months) were assessed at clinic entry (T0), after CDP (T1), and at 1- and 2-year follow-up (T2, T3). Based on the T1 assessment (decision criteria for DBT-A: ≥ 3 BPD criteria & ZAN-BPD ≥ 6), participants were allocated into three groups; CDP only (n = 74), CDP + DBT-A (eligible and accepted; n = 36), CDP no DBT-A (eligible, but declined; n = 17). Results: CDP only showed significantly fewer BPD criteria (T2: β = 3.42, p < 0.001; T3: β = 1.97, p = 0.008), higher levels of psychosocial functioning (T2: β = -1.23, p < 0.001; T3: β = -1.66, p < 0.001), and lower severity of overall psychopathology (T2: β = 1.47, p < 0.001; T3: β = 1.43, p = 0.002) over two years compared with CDP no DBT-A, while no group differences were found with regard to NSSI and suicide attempts. There were no group differences between CDP + DBT-A and CDP no DBT-A, neither at T2 nor at T3. Discussion: The findings support the decision criterion for the offer of a more intense therapy after CDP. However, there was no evidence for the efficacy of additional DBT-A, which might be explained by insufficient statistical power in the current analysis.
Gesehen am 22.11.2024